Analysis of Rubberized Concrete Deck Slab for different Bridge Structures as Per IRC Loadings : A Review - Aditya, K.; Kotecha, K. Divya; Singh, Yogesh (International Journal of Scientific Research in Civil Engineering, 2020)
Bridge is an important structure required for the transportation network. Now a day with the fast innovation in technology the conventional bridges have been replaced by the cost effective structured system. For analysis and design of these bridges the most efficient methods are available. Different methods which can be used for analysis and design are AASHTO, Finite element method, Grillage and Finite strip method.In this study we are presenting literature survey of papers related to utilization of advances in bridge designing and materials.
Keywords: Staad Beava; Irc; Vehicle; Bridge; Stresses; Deflection; Rubberized Concrete